2012
DOI: 10.1111/j.1476-5381.2011.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycine, a simple physiological compound protecting by yet puzzling mechanism(s) against ischaemia–reperfusion injury: current knowledge

Abstract: Ischaemia is amongst the leading causes of death. Despite this importance, there are only a few therapeutic approaches to protect from ischaemia-reperfusion injury (IRI). In experimental studies, the amino acid glycine effectively protected from IRI. In the prevention of IRI by glycine in cells and isolated perfused or cold-stored organs (tissues), direct cytoprotection plays a crucial role, most likely by prevention of the formation of pathological plasma membrane pores. Under in vivo conditions, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 150 publications
(284 reference statements)
1
39
0
1
Order By: Relevance
“…The majority of these are due to primary signaling or anti-inflammatory effects [11,14] not associated with necrosis and cannot be covered in detail within the confines of this review. Additional references to studies of glycine effects during diverse disease processes can be found in other reviews [10,11,1315]. However, a number of effects in which cytoprotection could be a primary target or during which necrotic cell damage is a major component merit more detailed consideration in the context of this review’s focus.…”
Section: Glycine Effects On Disease Models In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these are due to primary signaling or anti-inflammatory effects [11,14] not associated with necrosis and cannot be covered in detail within the confines of this review. Additional references to studies of glycine effects during diverse disease processes can be found in other reviews [10,11,1315]. However, a number of effects in which cytoprotection could be a primary target or during which necrotic cell damage is a major component merit more detailed consideration in the context of this review’s focus.…”
Section: Glycine Effects On Disease Models In Vivomentioning
confidence: 99%
“…glycine cytoprotection [5]. The contexts, mechanisms and relevance of glycine cytoprotection to necrotic cell death in vitro and in vivo have since been addressed in several hundred papers and reviews [6–15]. As we will cover here, this robust and widely replicated behavior that is expressed in multiple forms of necrotic cell damage to parenchymal, vascular, and inflammatory cells of diverse tissues has the potential to play a critical role in the development of immunogenic tissue injury and resulting disease processes.…”
Section: Introductionmentioning
confidence: 99%
“…Copper itself has complex metabolic interactions with other divalent cations, such as iron and zinc, which are especially evident during inflammatory states [24,25] . There may be amelioration of some of these effects with supplemental glycine [36] . Importantly, detoxification or conjugation processes can deplete glycine availability, for example, through excessive consumption of a preservative such as benzoic acid, frequently used as a food preservative, or a high-protein diet [13,38] .…”
Section: Responding To Stressmentioning
confidence: 99%
“…This protection may be enabled in part through a TLR4 receptor mechanism [35] . The protective effect of glycine in the responses of the liver to challenge show time and dose-related complex considerations that would be difficult to identify with confidence unless looked for specifically [36] . Indeed, the metabolic roles played by glycine in vivo are so many and fundamental that the systems to ensure its ready availability are well protected and buffered [13] .…”
Section: Responding To Stressmentioning
confidence: 99%
“…These processes are most likely to be limited by the availability of conditionally essential amino acids - prominently proline and glycine. This is especially likely to be problematic during periods when there are competitive demands (inflammation, infection, and xenobiotic challenge) [8,9]. He also emphasized the potential linkage between glycine (both in terms of its role in growth and as an excitatory and inhibitory neurotransmitter), growth, and cognitive outcomes [10].…”
Section: Session Summarymentioning
confidence: 99%